Network disruption detected in VE (Venezuela) - Voidly (2026)
CRITICAL severity mixed detected in Venezuela. Confidence: 70%. Data sourced from CensoredPlanet, IODA.
Censorship Incident ID: VE-2026-0004
Keywords: censorship; VE; mixed; critical